Take back the truth confronting Papal power and the religious right - Manning, Joanna 1943- (Crossroad Pub., 2002)
"Joanna Manning introduces readers to the growing polarization within Christianity and its relationship with the modern world. She warns against the ongoing retreat into fundamentalism and exclusivity and points the way toward inclusivity and compassion."--Jacket.